2015
DOI: 10.1108/bfj-04-2014-0147
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes of cactus pear fruit and their role in consumer choice

Abstract: Purpose – The purpose of this paper is to detect what experience and credence quality attributes contribute to the consumer decision to consume cactus pear fruit. The authors therefore try to measure the effect of each quality attribute on consumer choice. Design/methodology/approach – As a theoretical basis, two principal quality attributes emphasised in the literature on consumer behaviour were analysed and adjusted to the specific fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 59 publications
1
34
0
1
Order By: Relevance
“…Bruhn (1995) identified firmness and external color of peaches as the most important attributes for consumers to judge the internal quality of fruit. Migliore et al (2015) showed that the quality attributes such as color, number of seeds, and ease of peeling are more important for cactus pear fruit.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruhn (1995) identified firmness and external color of peaches as the most important attributes for consumers to judge the internal quality of fruit. Migliore et al (2015) showed that the quality attributes such as color, number of seeds, and ease of peeling are more important for cactus pear fruit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other than sensory attributes, credence attributes also play an important role in consumers' fruit and vegetable consumption. Studies conducted in various countries have found that credence attributes, such as price, origin, production methods, and quality indicators, are essential drivers of fruit purchases (Campbell et al 2013;Moor et al 2014;Migliore et al 2015). Among all the credence attributes, COO is one of the most important attributes of food products (Caswell 1998;Yu et al 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recognizing product attributes that are important to the consumers plays a significant role in product marketing. For example, Galati, Romeo, Crescimanno, and Schifani (2015) found the attributes of cactus pear fruit largely explained consumers' decisions to consume the fruit. However, consumers' perception of the attributes of blueberries remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic attributes refer to the physical characteristics of the product and are further categorized as search attributes, such as freshness, colour, and size; experience attributes, such as taste, aroma, and ripeness, identify only after consuming the product (Badar et al 2015;Di Vita et al 2017;Cembalo et al 2015). Extrinsic attributes do not refer to the physical characteristics of the product, and consumers consider them increasingly important during the process of choice (Schifani et al 2016;Migliore et al 2015). They include food safety, environmentally friendly production, and provenance (Moor et al 2014;Dekhili and d'Hauteville 2009).…”
mentioning
confidence: 99%